Women's employment, income and divorce in West Germany: a causal approach - Daniel Brüggmann (Journal for Labour Market Research, 2020)
In this paper, I assess the employment and income effect of divorce for women in West Germany between 2000 and 2005. With newly available administrative data that allows me to adopt a causal approach, I find strong negative employment effects with respect to marginal employment and strong positive effects with respect to regular employ-ment. However, in sum, the overall employment rate (marginal and regular employment combined) is not affected. Furthermore, the lower the labor market attachment before separation is, the more pronounced employment effects are. In addition, I also estimate the impact of divorce on daily gross incomes. I find no convincing evidence for an income effect. I conclude that a divorce might have a pure labor supply effect only.
Keywords: C14; J3; J12; J22; 330; Divorce; Female employment; Propensity score matching; Difference-in-difference; Boosted regression; Principal stratification; Sample selection